No. 8 in Union Oil Company's Natural Color Scenes of the West - Pacifica Statue (Union Oil Co.)
Brilliant Court of the Pacific scintillates for the second year on Treasure Island. A rainbow of night illumination, the sixty-million dollar Golden Gate International Exposition is a spectacular pageant dedicated to knowledge, leisure, travel.